War valley [large type] - Hill, Lancaster, 1951- (A Hank Gannon western, 2019)
In this powerful new series, a Confederate veteran heads west to start a new life-and gets caught in the middle of a new kind of war . . . WAR VALLEY Hank Gannon grew up on a Florida plantation. He fought alongside his brothers-in-arms in the Civil War. Then he joined the Texas Special Police to help build a more peaceful union-and a future for his beloved Constance. That was the plan. But when a prisoner dies in his custody, Gannon is forced to leave Austin and head into Comanche territory. Alone but undaunted, he meets up with Roving Wolf- who has just slain a former soldier from his unit. Gannon can't let the killing go unpunished. Even here, in this Godforsaken valley, the law must be upheld . . . On the one side is a bloodthirsty war party of Indians, heading for the white man's capital. On the other side is a makeshift army of Texas Special Police and the Texas State Guard, ready to meet the threat head-on. In the middle are Hank Gannon and Roving Wolf, waging their own blood feud. Two men trapped in a war. Fighting to survive their mutual hate. Killing to get out alive . . .